Towards responsible government in East Asia [ trajectories, intentions, and meanings - Li, Linda Chelan (Comparative development and policy in Asia series, 2009)
Explores the idea of responsible government in East Asia. This book shows how historically the concept of responsibility is more embedded in political discussions in Asia, whereas the concepts of democracy and accountability are more embedded in the intellectual traditions of Europe